EFFECT OF COMBINATION OF TWO PLANTS ON ANTI-OXIDANT ACTIVITY - Jose, Deepa; B, Prasanth; Baby, Sini (Journal of Biomedical and Pharmaceutical Research, 2019)
Anti-oxidants are essential for maintaining optimum health and well being by acting against damage caused by free radicals. Regular consumption of vegetables and fruits with anti-oxidant activity can reduce the risk of many chronic diseases. The main objective of the study was to evaluate the antioxidant activity of Psidium guajava and Syzygium cumini leaves individually and as a combination of ethanolic leaf extracts of both in 1:1 ratio. The antioxidant activity of ethanolic leaf extracts of Syzygium cumini and Psidium guajava and its 1:1 combination were determined by different methods such as Superoxide free radical scavenging assay, Hydrogen peroxide scavenging assay and Hydroxyl radical scavenging assay.The 1:1 combination of ethanolic leaf extract of Syzygium cumini and Psidium guajava showed higher antioxidant activity than the individual extracts. Out of the two individual extracts, Syzyium cumini showed more activity than the Psidium guajava extract. A dose dependent increase in activity was found in all methods. The percentage inhibition of combined extract by hydroxyl radical scavenging assay and hydrogen peroxide scavenging assay was 72.70 and 76.15 respectively. Superoxide free radical scavenging assay, showed inhibition of 63.5percentage.From the result it is concluded that leaves of both the plants possess anti-oxidant activity and Syzygium cumini exhibited more activity than Psidium guajava. But the combination of both is superior to individual extracts in exhibiting anti-oxidant activity. The results showed the possibility of synergistic or additive effect of combination of ethanolic extracts of Syzygium cumini and Psidium guajava leaves in the ratio 1:1.